Morphological Pattern of Ovarian Tumour : Experience in a Tertiary Level Hospital - Ahmed, Mousumi; Afroze, Nazma; Sabiha, Mahjabin (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background: Ovarian tumor is a common type of gynecological neoplasm and accounts for 15-25% of all gynecological malignancies. It is associated with high mortality and an accurate histological diagnosis is essential for management of patient. Objective: The study was performed to find out the morphological pattern, nature and age distribution of ovarian tumour in our hospital. Material and methods: It was a prospective study,conducted in the Department of Histopathology and Cytopathology, BIRDEM General Hospital, Dhaka for a period of two years from Jan 2014 to Dec 2015. This study included 186 cases of ovarian tumors sent in the Department of Pathology for histopathological evaluation. Non-neoplastic lesions and tumour-like conditions were excluded from the study. Histological diagnosis, age and laterality of ovary were recorded. Morphological pattern, nature and age distribution of ovarian neoplasms were calculated. Result: 84.95% cases of ovarian tumour were benign, 1.61% cases were borderline and 13.44% cases were malignant. ORIGINAL ARTICLES Surface epithelial tumour was the commonest type of tumour (61.83%), according to the histogenesis , followed by germ cell tumour. Benign serous tumour was the most common type of benign tumor (37.98% cases), followed by mature cystic teratoma (33.55% cases). Serous cystadenocarcinoma was the most common type of malignant tumour (36.0%), followed by endometrioid carcinoma (28.0%). Benign tumours were more frequent in all age group. The incidence of malignant ovarian tumour increased with age and was most frequent in >50 years age group. Benign tumours were commonly cystic, whereas malignant tumours were commonly solid and cystic. 11.23% cases of ovarian tumours were bilateral. Conclusion: Benign ovarian neoplasms were more common than malignant ones and benign serous tumour was the commonest type of benign neoplasm whereas serous cystdenocarcinoma was the commonest type of malignant neoplasm. The pattern and age distribution of ovarian tumour of our study were quite similar with other studies with some variation. J Bangladesh Coll Phys Surg 2018; 36(1): 5-10